673 Pre and Post Bronchodilator Airway Resistance Values in Children with Asthma Using Airflow Perturbation Device (Apd). (October 2012) - Rostami, N; Bautista, M; Johnson, A; Vossoughi, J; Kezsler, M
Abstract : Background: Asthma is the most common chronic disease of childhood and pulmonary function testing plays an important role in assessment and management of children with asthma. Pre and post bronchodilator spirometry test is the most common pulmonary function measurement that is utilized in the diagnosis of asthma. Methods: Respiratory resistance using APD was measured prior and 20 minutes after Albuterol in children with asthma who presented to the Pediatric Pulmonary Clinic at GUH. Results: A total of 30 children with asthma (mean age: 10.6; range: 5.6–17) including 14 female and 16 male participated in the study. The respiratory resistance values by APD ranged from 3.34–8.22 CmH2O/L/S (mean 5.27) for pre bronchodilator treatment and 2.37–6.95 (mean 4.33) for post treatment. All 30 children showed decrease in respiratory resistance as measured by APD after bronchodilator therapy. The highest value of resistance was 8.22 which was seen in the youngest child (5.6 yo) and the lowest resistance was 3.34 which was seen in an older child (16 yo). These results are consistent with the findings that airway resistance decreases after bronchodilator therapy in patients with asthmahas been developed to measure airway resistance noninvasively and without need of extensive coordination. The APD is a simple and portable device that can be used easily by patients of all ages. Conclusions: APD is a simple, convenient, effortless, and easy to use device that may be a used as a valuable tool in evaluation of children with asthma. This abstract is funded by NIH-NHLBI Grant # 2R44HL0780 55–02A1.